Clinical signs in small animal medicine - Schaer, Michael (Manson Publishing, 2008)
This book contains over 400 clinical cases representing the experience of the author's career in practice and as a university teacher. The cases, grouped broadly by subject, are presented by means of over 800 colour photographs of the highest quality, plus detailed captions focusing on key pointers to diagnosis and treatment. The underlying theme of the book is that the clinician's eye, thought processes and judgement will always be central to successful clinical practice. The book will appeal to all involved in medicine of the dog and cat--practitioners, instructors, trainees, students.